(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The article reveals the theoretical principles of anti-crisis management of the enterprise’s foreign economic activity. The essence of the concept of crisis is revealed. Attention is drawn to the importance of adaptive anti-crisis management aimed at responding to changes and using opportunities to ensure the sustainable development of the enterprise in the conditions of the external environment. The internal and external causes of the crisis are singled out. The classification, tasks, and main principles of anti-crisis management are substantiated. The key elements of managing the foreign economic activity of the enterprise in crisis conditions, as well as the main approaches to minimizing the impact of threats, are considered. Taking into account the importance of developing anti-crisis programs to prevent and overcome crises at the enterprise, the key methods of work to minimize the impact of threats to the enterprise’s foreign economic activity were analyzed, such as: minimizing threats through diversification, information search, risk management, interaction with the environment, control of the internal environment. Diversification approaches have been proven to be the most common and effective in protecting foreign economic activity, but require careful, long-term planning and significant financial investment. It is substantiated that obtaining timely information about the state of the market and the industry is an important step toward reducing threats. Attention is drawn to the fact that risk management covers a wider range of actions than crisis management, including identification, analysis, assessment, management, and mitigation of risks that may arise. Emphasis is placed on ensuring the appropriate level of resource reservation, which is aimed at maintaining the necessary stock of cash, raw materials, goods, and other necessary materials. The importance of establishing long-term partnership relations in the implementation of the enterprise’s foreign economic activity has been proven. It has been proven that a comprehensive approach to the creation of a system of anti-crisis management of the enterprise’s foreign economic activity should include the organization, planning, and implementation of not only specific competencies but also effective management tools that will help the enterprise adapt to changes and increase its competitiveness.